2019
DOI: 10.4236/ajibm.2019.912146
|View full text |Cite
|
Sign up to set email alerts
|

How Psychological Capital Promotes Innovative Behavior: A Mutilevel Modeling

Abstract: Based on conservation of resources theory, this study explores the impact of employee psychological capital on innovative behavior and the role of job embeddedness and internal social capital in this process. The results of cross-level data analysis show that psychological capital can effectively predict employee innovative behavior; psychological capital predicts employee innovative behavior through job embeddedness; internal social capital not only moderates the impact of psychological capital on job embedde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 47 publications
(45 reference statements)
0
15
0
3
Order By: Relevance
“…However, in this study, the focus on PsyCap was twofold: on the effects of PsyCap on hospital employees' IIB and on employees in the Norwegian context. According to previous studies, there is a positive link between PsyCap and innovative behavior [27,31,41,42]; this study proposes a positive relationship between PsyCap and IIB among hospital employees. This relationship can be formally stated as the following hypothesis: Hypothesis 1:Psychological capital (PsyCap) is positively related to individual innovative behavior (IIB).…”
Section: The Antecedents Of Individual Innovative Behavior (Iib)mentioning
confidence: 67%
See 2 more Smart Citations
“…However, in this study, the focus on PsyCap was twofold: on the effects of PsyCap on hospital employees' IIB and on employees in the Norwegian context. According to previous studies, there is a positive link between PsyCap and innovative behavior [27,31,41,42]; this study proposes a positive relationship between PsyCap and IIB among hospital employees. This relationship can be formally stated as the following hypothesis: Hypothesis 1:Psychological capital (PsyCap) is positively related to individual innovative behavior (IIB).…”
Section: The Antecedents Of Individual Innovative Behavior (Iib)mentioning
confidence: 67%
“…In addition, examining the role of PsyCap for working adults in the USA, Sweetman et al [41] found that PsyCap and all its HERO components were positively related to creative performance. Moreover, studying business graduates, leaders, and employees, Lan [27] found PsyCap to be positively related to IIB. However, in this study, the focus on PsyCap was twofold: on the effects of PsyCap on hospital employees' IIB and on employees in the Norwegian context.…”
Section: The Antecedents Of Individual Innovative Behavior (Iib)mentioning
confidence: 99%
See 1 more Smart Citation
“…Organisasi masa kini beroperasi dalam persekitaran yang amat mencabar yang memerlukan sumber manusia memiliki keupayaan atau kekuatan psikologi bagi meningkatkan prestasi kerja. Kajian terdahulu menunjukkan pekerja yang berpegang pada nilainilai yang positif, mempunyai keupayaan psikologi dan inovatif merupakan sumber manusia yang amat bernilai dan dapat memberi kelebihan daya saing kepada organisasi (Lan, 2019;Walumba, Peterson, Avolio & Hartnell, 2010). Hasil kajian terkini dalam bidang kelakuan organisasi positif menunjukkan bahawa konstruk modal psikologi berupaya mengukur kekuatan psikologi pekerja yang kritikal untuk pembaikan prestasi kerja dan inovasi organisasi (Okolie & Emoghene, 2019;Lan, 2019;Luthans & Youssef-Morgan, 2017;Luthans, Avolio, Avey & Norman, 2007).…”
Section: Pengenalanunclassified
“…Kajian terdahulu menunjukkan pekerja yang berpegang pada nilainilai yang positif, mempunyai keupayaan psikologi dan inovatif merupakan sumber manusia yang amat bernilai dan dapat memberi kelebihan daya saing kepada organisasi (Lan, 2019;Walumba, Peterson, Avolio & Hartnell, 2010). Hasil kajian terkini dalam bidang kelakuan organisasi positif menunjukkan bahawa konstruk modal psikologi berupaya mengukur kekuatan psikologi pekerja yang kritikal untuk pembaikan prestasi kerja dan inovasi organisasi (Okolie & Emoghene, 2019;Lan, 2019;Luthans & Youssef-Morgan, 2017;Luthans, Avolio, Avey & Norman, 2007). Pekerja dengan modal psikologi yang tinggi didapati berupaya menangani cabaran dalam pekerjaan, meningkatkan prestasi kerja dan mencapai kesejahteraan di tempat kerja (Luthans & Youssef-Morgan, 2017;Luthans & Youssef, 2007;Bakker & Schaufeli, 2008).…”
Section: Pengenalanunclassified